PIDANA PEMISKINAN KORUPTOR PADA TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Sugiarto, Agus (Universitas Wiralodra, 2020)
Corruption is a large and interesting problem as a legal matter concerning complicated crime types. It contains multiple aspects of economic relations, politics, social, and culture. Various efforts to eradicate corruption have been done. However, in terms of quantity and quality of the perpetrators the corruption is still increasing. It is necessary to prevent and reduce the occurrence of corruption cases. One of the discourses to tackle corruption in Indonesia is the impoverishment of corruptors. The research objective is to analyze the problems that have been formulated. The research method used is normative juridical with qualitative analysis. The results of the research and discussion of the thesis states that 1) the regulation of impoverishment of criminals against corruptors as one of the alternative sentences in corruption in Indonesia has not been explicitly regulated in legislation to eradicate corruption; 2) the obstacles faced in the application of criminal impoverishment or payment of compensation money for state financial losses of corruptors is difficult. It is difficult to find wealth owned by corruptors, either because it is hidden by means of naming other names, or indeed the convicted of corruption does not have any wealth.